PENDEKATAN CULTURE INDEPENDENT UNTUK ANALISIS KOMUNITAS BAKTERI - Nur Fitriah Afianti; Yeti Darmayati (OSEANA, 2019)
CULTURE INDEPENDENT APPROACH FOR BACTERIAL COMMUNITY ANALYSIS. Analysis of bacterial community can be through two approaches, through cultivation (culture dependent) and without cultivation (culture independent). Culture dependent approach is conventional method which only covered few bacteria because not all bacteria could be cultured. Culture independent approach with molecular techniques based on DNA communities can provide more information about the structure and diversity of bacteria in nature, both culturable bacteria and unculturable bacteria. 16S rRNA gene is commonly target gene used in bacterial communities analysis. Other specific target genes also being developed for specific groups of bacteria. Several methods are developed for the analysis of molecular markers 16S rRNA or other specific genes, including Denaturing Gradient Gel Electrophoresis (DGGE), Terminal Restriction Fragment Length Polymorphism (TRFLP), and Single Strand Conformation Polymorphism (SSCP).